Revolutionizing Early Childhood Development Screening with the PINKI App - Jayadi, Usman; Afrilia, Dian; Suryaningtyas, Winda; Khodijah, Salma (International Journal Scientific and Professional, 2025)
Early childhood development is a critical phase shaping a child's future, making monitoring their progress essential to identify developmental concerns. However, many early childhood educators (PAUD teachers) face significant barriers to performing accurate and timely screenings due to limited tools and knowledge. This research investigates the effectiveness of the Pinki app, a digital tool designed to streamline and enhance the process of child development screening in early childhood education settings. The study involved a group of PAUD teachers trained to use the Pinki app to assess children's cognitive, motor, and social-emotional development. The research aimed to evaluate the impact of the app on the accuracy, efficiency, and effectiveness of developmental screenings. Data was collected through pre- and post-training surveys, interviews with teachers, and analysis of the screening results generated by the app. The findings significantly improved teachers' ability to conduct systematic, data-driven assessments. 85% of teachers reported enhanced confidence in their ability to identify developmental issues early, and 78% noted that the app helped them save time while increasing the accuracy of their evaluations. Furthermore, the Pinki app enabled early intervention strategies by providing clear, objective data on children's development, contributing to more effective support for children with developmental delays. Despite challenges such as limited resources and occasional connectivity issues, the study demonstrated that integrating digital tools like the Pinki app can transform early childhood education by enhancing the quality of developmental monitoring and fostering better educational outcomes. This research highlights the potential for technology-driven interventions to address gaps in early childhood education and improve long-term developmental outcomes for children.